Developing an efficient and optimized irrigation plan under varying water-supply regimes - Purushottam Agrawal; Jitendra Sinha; Nilima Jangre; Fanesh Kumar; Kamalkant; Alok Sinha; Ashwin Singh; Ashes Banerjee; Akella Satya Venkatesh; Srinivas Pasupuleti (Ain Shams Engineering Journal)
Crop development relies on water availability, needs, and application, necessitating large irrigation projects to ensure sustainable and equitable agriculture in the long term. This study investigates water losses and gaps during paddy cultivation in India’s tropical semi-arid region, where agriculture is the primary economic driver for communities. Given the population’s heavy reliance on rice, paddy cultivation was closely examined to identify irrigation-related vulnerabilities. An optimal irrigation plan was developed based on the analysis of the current water supply scenario for four different paddy production situations: 1) Rainfed (10 ha), 2) Rain + Canal irrigated (2174 ha), 3) Rain + Borewell + Rivulet irrigated (165 ha), and 4) Rain + Canal + Borewell irrigated (243  ha). The dependable water availability from rains and canals was calculated at a 75 % probability of exceedance to formulate an optimal water supply for the crop. Under this plan, the required water depth is reduced from 32.9  mm to 7.4  mm, saving 0.6167  Mm3 of water. In areas with optimized canal supply, no borewell water is needed for the canal-irrigated land supported by borewells (243  ha).